Deformaciones artificiales del cráneo en cazadores-recolectores del Holoceno medio-tardío del Noroeste de Patagonia - Pérez, Sergio Iván (2009)
The aim of this paper is to analyze the variation in artificial cranial deformation of northwestern Patagonia and to incorporate it into the discussion about the patterns of temporal and spatial variation on a supra-regional scale. We analyzed a sample of 28 adult skulls from archaeological sites from the province of Neuquén. For comparative purposes we also included 12 samples from Pampean Region and northeast and center of Patagonia. The variation in artificial deformation was described using coordinates of landmarks and semilandmarks in 2 dimensions within the context of geometric morphometric techniques. The results indicate the existence of a marked temporal variation in artificial cranial deformations in Neuquén. Sites dated ca 4000 years BP are characterized by compression in the occipital region and frontal bones. This morphology is also found in burials from northern Atlantic coast of Patagonia and South East Pampean Region with chronologies post 3300 years BP. The individuals dated within the final late Holocene show morphologies are characterized by the expansion of the frontal bone and that compression in lambda. The same type of deformation is contemporaneously found in Chubut River and South Pampa. In summary, our results allow to extend the temporal depth of the artificial deformation in northern Patagonia to the limit of late-middle Holocene, highlighting the supra-regional geographic distribution of cranial deformations.